PENGARUH FASILITAS KANTOR, MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA KECAMATAN BANYUBIRU KABUPATEN SEMARANG (Studi Kasus Di Desa Gedong, Kebumen, Dan Rowoboni) - Royani, Sardevi Ita; Safitri, Unna Ria; Hegy Suryana, Alean Kistiani; Purwanto, Hari (EKOBIS, 2024)
ABSTRACT The purpose of this study was to determine office facilities, work motivation, and work discipline on the performance of village officials in Banyubiru District, Semarang Regency. The population in this study is 60 (sixty) village officials. Sampling using saturated or census sampling technique, the research method used is quantitative methods. testing data instruments with validity and reliability tests, data analysis using normality tests, heteroscedasticity tests, autocorrelation tests, multicollinearity tests, with Durbin Watson tests and hypothesis testing to find out between variables that have a significant relationship. The results showed that the multiple regression analysis obtained the equation: Y = 23.183 + 0.094 + 0.196 + 0.011 + e. The F test shows that it is significant 0.187. Partially (t test) office facilities variable obtained a significance of 0.000, work motivation variable obtained a significance of 0.491 and work discipline variable obtained a significance of 0.928. The coefficient of simultaneous determination (R2) between office facilities, work motivation, and work discipline on the performance of village officials is 0.032 or 3.2%. it can be concluded that all independent variables simultaneously affect the dependent variable. Keywords: Office facilities, work motivation, work discipline, performance.